Synthesis of 3-Oxazolines via SnCl4-Promoted Formal [3+2] Cycloaddition of Donor–Acceptor Oxiranes and Nitriles - Zhou, Hai; Zeng, Xiaofei; Xie, Yan; Zhong, Guofu (Synlett, 2015)
A novel SnCl4-promoted formal [3+2] cycloaddition of donor–acceptor oxiranes and nitriles via chemoselective C–C bond breakage was developed. This reaction provides an efficient and practical method for the preparation of 3-oxazolines in good yields (up to 89%).
Keywords: synthesis; 3-oxazoline; formal [3+2] cycloaddition; oxirane; nitrile